Evolution and mechanism of the mitochondrial cox1 intron horizontal transfer in Angiosperms - Ceriotti, Luis Federico (2017)
The most frequent case of horizontal gene transfer in angiosperms involves the group I intron in the cox1 mitochondrial gene, originally acquired from a fungal donor and followed by more than 100 subsequent inferred plant-to-plant transfer events. This promiscuous behaviour is thought to be due to its encoded DNA homing endonuclease, whose cleavage site is in cox1 intron-less alleles. The study of homologous introns in yeast suggests that intron insertion occurs through the double-strand break repair (DSBR) pathway without crossover, process called intron homing. So, this mechanism has been proposed to participate in angiosperms cox1 intron propagation. However, other repair mechanisms supposed to occur in plant mitochondria could participate. These mechanisms can be distinguished because they are supposed to generate crossovers (CO) and/or non-crossovers (NCO) in different proportions. In order to detect possible alternative repair mechanisms involved in cox1 intron propagation, we analyzed 139 angiosperm species with the intron. The analysis consisted in the identificationof CO and NCO events comparing exon1, exon2 and intron phylogenetic relationships. When sequences were available the analyses was extended to intergenic regions flanking the exons. In contrast with original DSBR model, where COs and NCOs are expected to occur in similar proportions, only NCO events where detected in our analyses. We propose an alternative repair pathway called synthesis-dependent strand annealing (SDSA), which can only produce NCO results, as the most probable mechanism involved in the cox1 intron propagation in angiosperms.